Caregivers of patients with disorder of consciousness: burden, quality of life and social support. (24th March 2015) - Giovannetti, A. M.; Covelli, V.; Sattin, D.; Leonardi, M.
<x xml:space="preserve">Abstract</x> Objective To evaluate quality of life (QoL) and its predictors, psychological burden and level of perceived social support in caregivers of patients with disorder of consciousness. Materials & Methods World Health Organization Quality of Life‐Bref (WHOQOL‐BREF), State Trait Anxiety Inventory‐Y (STAI‐Y), Beck Depression Inventory (BDI‐II), Prolonged Grief Disorder Questionnaire, Coping Orientations to Problem Experiences, State‐Trait Anger Expression Inventory‐2 (STAXI‐2), and the Medical Outcome Study Social Support Survey (MOS‐SSS) were administered. One‐sample t‐tests were performed to compare WHOQOL‐BREF, STAI‐Y and STAXI‐2 mean scores to the respective normative sample (NS). Pearson correlation was calculated between time dedicated to patient's care, WHOQOL‐BREF, BDI‐II, STAI‐Y and MOS‐SSS scores. Hierarchical multiple regression analyses were performed to evaluate which variables have predictive power on QoL. Results A total of 129 caregivers, 68.2% female, mean age 52.8 years, were enrolled. Three WHOQOL‐BREF domains were significantly lower. Anxiety and anger were in line with NS. 28.7% of the sample reported high level of depressive symptoms; 20.9% satisfied the prolonged grief disorder criteria. No differences emerged between caregivers and chronic ill patients' scores at MOS‐SSS. STAI‐Y, BDI‐II and WHOQOL‐BREF scores positively correlated. MOS‐SSS domains inversely correlate with BDI‐II scores. BDI‐II results the most relevant predictor of QoL. Conclusions Study results provided innovative information about caregivers' poor QoL, difficulties in social support and high levels of burden. Time dedicated to care is not strictly related to burden, while social support perceived is highly associated with caregivers' depressive symptoms that are strong predictor of poor QoL. Supportive intervention able to integrate psychological, social and environmental levels is needed.